2015
DOI: 10.1111/ajt.13157
|View full text |Cite
|
Sign up to set email alerts
|

Improved Revascularization of Islet Grafts Using an Angiogenic Monocyte Subpopulation Derived From Spheroid Culture of Bone Marrow Mononuclear Cells

Abstract: y Both authors contributed equally to this manuscript.The spheroid culture method is an effective strategy for ex vivo expansion of an autologous therapeutic cell population. We investigated if cotransplantation of bone marrow-derived spheroids (BM-spheroid) formed using 3D culture of BM-derived mononuclear cells (BMMNCs) could improve the posttransplant outcome of islet grafts using a mouse syngeneic marginal mass renal subcapsular islet transplantation model. Using green fluorescent protein transgenic (GFP-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These homeostatic effects of macrophages in BMNCs suggest that increasing the number of cells responsible for maintenance of joint health may restore joint homeostasis by tipping the balance back toward an anabolic state. BMNCs provide potent antiinflammatory and regenerative effects in injured tissues, including those with minimal regenerative capacity, such as the pancreas, CNS, and osteochondral defects (44)(45)(46)(47)(48)(49). BMNCs can also induce resolution of inflammation in chronically inflamed tissues refractory to other treatments, such as in joints and the respiratory system (39,50).…”
mentioning
confidence: 99%
“…These homeostatic effects of macrophages in BMNCs suggest that increasing the number of cells responsible for maintenance of joint health may restore joint homeostasis by tipping the balance back toward an anabolic state. BMNCs provide potent antiinflammatory and regenerative effects in injured tissues, including those with minimal regenerative capacity, such as the pancreas, CNS, and osteochondral defects (44)(45)(46)(47)(48)(49). BMNCs can also induce resolution of inflammation in chronically inflamed tissues refractory to other treatments, such as in joints and the respiratory system (39,50).…”
mentioning
confidence: 99%
“…The 3D culture models allow various cells to behave more like in vivo cells, providing enhanced therapeutic efficacy (25) and local persistence of therapeutic cells (26). In the current study, the robust angiogenic efficacy of the BM-spheroids in our previous study (12) was reproduced in more clinically relevant intraportal islet transplantation models, and the BM-spheroids did not evoke portal thrombosis even when the infused cell number far exceeded the number of MSCs that caused liver infarction after intraportal injection in parallel experiments.…”
Section: Discussionmentioning
confidence: 56%
“…In this context, cotransplantation of bone marrow-derived mononuclear cells (BM-MNCs) and early or late endothelial progenitor cells with islets has been attempted and has shown promising results in small animal models (6)(7)(8)(9), although the scarcity of the therapeutic cell population has been an obstacle to this approach. Recently, we tested a strategy to expand an autologous therapeutic cell population that possesses higher angiogenic or paracrine activities (10,11), namely, cotransplantation of islets with spheroids formed by selective ex vivo proliferation of the highly angiogenic CD31 + CD14 + CD34 + monocyte subset via a three-dimensional (3D) culture technique that uses a high cell density and nonattachable culture system (12). In our previous study, highly angiogenic bone marrowderived spheroids (BM-spheroids) not only had robust angiogenic capacities, and actively participated in vessel formation in vivo, but also improved the survival and function of islet grafts in a mouse syngeneic marginal mass renal subcapsular islet transplantation model (12).…”
mentioning
confidence: 99%
“…Another study demonstrated that bone marrow-derived mononuclear cells can be cultured into spheroids, with CXCR4+CD31+ myeloid cells being the main cell components. In the islet transplantation model under the renal capsule of syngeneic mice, cotransplantation of bone marrow–derived spheroids improves the blood supply reconstruction and graft function ( 66 ). Although research on macrophages from different sources in innate immune response in the field of islet transplantation remains limited, existing studies have provided initial insights into the influence of monocytes with different functions on islet transplantation.…”
Section: Macrophage Origins In Islet Transplantationmentioning
confidence: 99%